Persepsi Ayat-ayat Misogini dalam Surat Al-Nisa’ terkait Kesetaraan Gender (Studi Kasus pada Ibu-Ibu Aisyiyah Socah) - Endriyati, Enni; Hasan, Dony Burhan Noor (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Women, with the grace of Allah SWT and under the message of Islam, were returned to their noble position as the commander of justice and protector of Islam. This can be seen in several religious texts in Islam, both in the form of the text of the Qur’an and the Hadith of the Prophet which glorify the nature of women themselves. However, in several texts of the Qur'an, verses are found that are suspected and considered to degrade the position of women, especially in the letter Al-Nisa’, according to Sayyid Rasyid Ridha, this surah is called Al-Nisa’ because at the beginning of its opening it talks about women and the laws relating to them. Therefore, a study or research is needed that highlights women’s views on themselves regarding the concept of gender equality which has been fought for so hard by feminists. This research with a qualitative descriptive approach tries to reveal the views of Aisiyah Socah’s regarding gender equality issues and their relationship to their understanding of religious texts that contain misogynistic elements. The results of the study show that the concept of gender equality that has been echoed by scientists and feminists has not been fully understood by most of the mothers of Aisyiyah Socah. The responses of ‘Aisyiyah Socah to the content of the verses of the Qur’an in the letter Al-Nisa which seem to contain gender bias can be said to be quite diverse. In general, they strongly believe in and apply the concept of equality in their respective family lives.